Lots to spot Flashcards Nature - Kelly,Miles (Miles Kelly, 2022)
Lots to Spot Flashcards: Nature! is a lovely set of double-sided flashcards, designed to engage young children as they learn numbers, colours and words about the natural world around them. One side features an illustration of something your child might find on a nature walk, such as 'leaf', 'swan' or 'pine cone'. The other side shows a number and a colour. For example, on the 'frogs' card, the back of the card features the number '5', an illustration of 'five green frogs' and the background colour is green. Each card also features a 'Spot the odd one out' activity for children to enjoy.
Keywords: Flashcards